Usability of Tea Waste in Concrete as Natural Fiber - Cuma Kara (Doğal Afetler ve Çevre Dergisi)
In this study, the effect of tea waste (CA) obtained from Artvin-Borçka Muratlı tea factory as natural fiber on the fresh and hardened properties of the concrete was investigated. For this purpose, C20 / 25 class concrete was produced, then 0, 1, 3, 5, 7 and 9 kg tea waste was reinforced into 1 m3 mix and thus 6 different concrete types (CA0, CA1, CA3, CA5, CA7, CA9) were prepared. After determining the amount of collapse and the air content, the CA-reinforced fresh concrete was placed in molds of 100 mm x 100 mm x 400 mm, 150 mm x 150 mm x 150 mm and 70.7 mm x 70.7 mm x 70.7 mm. On the 7th and 28th day, the capillary water absorption, concrete test hammer, ultrasonic pulse velocity, flexural strength, compressive strength and abrasion resistance tests were performed to the concretes held in the appropriate curing environment. As a result, it was determined that the reinforcing concrete with CA increased the need for water, filled the gaps in the concrete and that the ultrasonic pulse velocity, concrete test hammer, flexural strength and compressive strength values were increased with the use of up to 7 kg waste in 1 m3 concrete. When more than 5 kg of waste was used in 1 m3 concrete, it was seen that the amount of abrasion was increased while the water absorption was decreased. As a result, it was concluded that up to 7 kg tea wastes in 1 m3 concrete could be used as natural fiber, but it would be appropriate to use up to 5 kg in places where there might be exposion to abrasion.